2019
DOI: 10.1109/access.2019.2928633
|View full text |Cite
|
Sign up to set email alerts
|

Limited Feedback Designs for Machine-Type Communications Exploiting User Cooperation

Abstract: Multiuser multiple-input multiple-output (MIMO) systems are a prime candidate for use in massive connection density in machine-type communication (MTC) networks. One of the key challenges of MTC networks is to obtain accurate channel state information (CSI) at the access point (AP) so that the spectral efficiency can be improved by enabling enhanced MIMO techniques. However, current communication mechanisms relying upon frequency division duplexing (FDD) might not fully support an enormous number of devices du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Thus, if we use an antenna-combining method associated with the quantization process, such as quantization-based combining (QBC) [ 10 ], conventional SCVQ will not provide a close approximation. QBC is an effective antenna-combining method that reduces the quantization error caused by limited feedback using multiple receive antennas, and it has been widely employed to enhance feedback performance [ 24 , 25 , 26 , 27 ]. Thus, if we have an appropriate analytical model, such as SCVQ appropriate for QBC, it can be effectively used to evaluate the performance of various complicated MIMO systems utilizing QBC.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, if we use an antenna-combining method associated with the quantization process, such as quantization-based combining (QBC) [ 10 ], conventional SCVQ will not provide a close approximation. QBC is an effective antenna-combining method that reduces the quantization error caused by limited feedback using multiple receive antennas, and it has been widely employed to enhance feedback performance [ 24 , 25 , 26 , 27 ]. Thus, if we have an appropriate analytical model, such as SCVQ appropriate for QBC, it can be effectively used to evaluate the performance of various complicated MIMO systems utilizing QBC.…”
Section: Introductionmentioning
confidence: 99%
“…Enabled by device-to-device (D2D) communications, the conventional cooperation mechanism is developed in [40], [41]. CSI magnitude and phase are separately fed back, rather than together as complex channel gains.…”
Section: Introductionmentioning
confidence: 99%
“…The effective single antenna channel provides analytic flexibility in limited feedback systems. By using its flexibility, QBC has been widely investigated in various wireless applications [ 19 , 20 , 21 , 22 , 23 ]. Compared to ZFBF, the number of feedback bits is significantly reduced to combine with the block diagonalization beamforming in [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In [ 22 ], the QBC scheme is applied to orthogonal frequency division multiplexing systems by using subcarrier grouping. In a recent study, and with user cooperation, the QBC scheme was applied to a machine type communication networks [ 23 ]. This demonstrated that the QBC scheme is of benefit in various networks; however, its potential gain has not been investigated in actual cellular networks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation